Effectiveness of ERKADUTA model to increase stunting prevention behaviors among mothers with toddlers in Indonesia: A quasi-experiment - Sutinbuk, Dedek; Nugraheni, Sri A.; Rahfiludin, Mohammad Z.; Setyaningsih, Yuliani (Narra J, 2024)
Stunting, a persistent nutritional issue arising from prolonged inadequate nutrient intake, poses substantial risks such as heightened morbidity, mortality, and compromised cognitive, psychomotor, and verbal development. In Indonesia, addressing stunting in children under two necessitates urgent community empowerment, given its multifaceted nature. The aim of this study was to assess the effects of an intervention targeting mothers of toddlers, called RT kawal baduta (ERKADUTA) model, a local community-based assistance for babies under two years old. A quasi-experiment using pre-test and post-test with a control group design was conducted. Employing a quantitative analytic approach with 112 respondents, the effectiveness of ERKADUTA model to improve the knowledge, attitude, and practice of stunting prevention among mothers with child under two years old was assessed. ERKADUTA program was run for three months. The Wilcoxon test was used to determine score changes before and after program in both groups, while the Mann-Whitney test was used to analyze the score differences of knowledge, attitude and practice between intervention and control groups. Our data indicated that there were changes in knowledge, attitudes, and practices in preventing stunting in both the intervention and control groups. There are significant differences in knowledge (p<0.001, effect size=-0.855), attitude (p<0.001, effect size=-0.864), and practice score (p<0.001, effect size=-0.924) between the intervention and control groups after the intervention. This study highlights that the ERKADUTA model emerged as a potent catalyst in improving stunting prevention behaviors among mothers with toddlers and this model holds promise for addressing the complexities of stunting in Indonesia.